2014
DOI: 10.1128/genomea.01202-13
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Asaia sp. Strain SF2.1, an Important Member of the Microbiome of Anopheles Mosquitoes

Abstract: Asaia spp. are abundant members of the microbiota of Anopheles mosquitoes, the principle vectors of malaria. Here, we report the draft genome sequence of Asaia sp. strain SF2.1. This strain is under development as a platform to deliver antimalarial peptides and proteins to adult female Anopheles mosquitoes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Signal sequences predicted by PRED-TAT are in bold. Protein identification was made using NCBI BLAST focusing on the Asaia SF2.1 genome sequence [ 38 ]. If a hypothetical protein was detected with the Asaia genome, another BLAST was performed using the entire NCBI database.…”
Section: Resultsmentioning
confidence: 99%
“…Signal sequences predicted by PRED-TAT are in bold. Protein identification was made using NCBI BLAST focusing on the Asaia SF2.1 genome sequence [ 38 ]. If a hypothetical protein was detected with the Asaia genome, another BLAST was performed using the entire NCBI database.…”
Section: Resultsmentioning
confidence: 99%
“…sp. SF2.1 (NCBI assembly ID GCF_000505765.1), 58 Asaia prunellae JCM 25354 (GCF_000613885.1), As. platycodi JCM 25414 (GCF_000614545.1), and As.…”
Section: Discussionmentioning
confidence: 99%
“…Acetate and lactate are oxidized to carbon dioxide and water but the activity was considered low. Partial sequences of nifH ‐like genes from several isolates and Asaia type strains were obtained and, as well as their genomes , are deposited at GenBank . Noteworthy, up to date blast analysis revealed that these sequences blast only among them and with several partial nifH ‐like sequences from unculturable clone or chlorophyllide reductase subunit X ( bchX ) partial gene sequences from several microbial genome or unculturable clones (Fig.…”
Section: Asaiamentioning
confidence: 99%